2007
DOI: 10.1016/j.pbb.2007.07.017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of concurrent administration of (±)3,4-Methylenedioxymethamphetamine and cocaine on conditioned place preference in the adult male rat

Abstract: Conditioned place preference (CPP), a commonly used model for studying the role of contextual cues in drug reward and drug seeking, was employed to explore possible behavioral interactions between (±)3,4-methylenedioxymethamphetamine (MDMA; "ecstasy") and cocaine. On each of four occasions, adult male rats received one of three doses of MDMA (0 mg/kg, 5 mg/kg, 10 mg/kg; administered subcutaneously [s.c.]) combined with one of three doses of cocaine (0 mg/kg, 2.5 mg/ kg, 5 mg/kg; administered intraperitoneally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
1
12
0
1
Order By: Relevance
“…In addition, a similar trend has also been observed in rodents when given different substances of abuse. For instance, MDMA produced CPP in rats at a dose of 5 mg/kg, but at 10 mg/kg, there was a return to baseline (control) performance levels (Diller et al 2007). Methamphetamine produced biphasic effects either on locomotion (Huang et al 2012) or on CPP paradigm with low doses producing reward and high doses aversion (Cunningham and Noble 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a similar trend has also been observed in rodents when given different substances of abuse. For instance, MDMA produced CPP in rats at a dose of 5 mg/kg, but at 10 mg/kg, there was a return to baseline (control) performance levels (Diller et al 2007). Methamphetamine produced biphasic effects either on locomotion (Huang et al 2012) or on CPP paradigm with low doses producing reward and high doses aversion (Cunningham and Noble 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the present results support recent reports that the combined acute administration of MDMA and cocaine may produce greater locomotor activation and enhance dopaminergic responses to a greater extent than either drug administered separately, but the combined effects of these drugs depend on the particular dose combination. A review of the published literature revealed only two previous studies that have explored the combined acute effects of MDMA and cocaine (Diller et al 2007;Daza-Losada et al 2009). Diller et al (2007) assessed the concurrent administration of cocaine and MDMA on CPP in adult male Sprague-Dawley rats.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the published literature revealed only two previous studies that have explored the combined acute effects of MDMA and cocaine (Diller et al 2007;Daza-Losada et al 2009). Diller et al (2007) assessed the concurrent administration of cocaine and MDMA on CPP in adult male Sprague-Dawley rats. In that study, MDMA (0, 5.0, or 10 mg/kg) was administered 25 min prior to cocaine (0, 2.5, or 5.0 mg/kg) injections, in order to allow for the peak actions of cocaine and MDMA to occur simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important aspect is the temporal pattern of drug administration employed. Until now, most studies have focused on acute administration (Braida & Sala, 2002;Daza-Losada et al, 2009a;Diller et al, 2007;Manzanedo et al, 2010;Robledo et al, 2007), though there is a growing number of studies employing repeated administration and studying long-term effects (AchatMendes et al, 2003;Daza-Losada et al, 2008a, 2008bEstelles et al, 2006;Jones et al, 2010;Ribeiro Do Couto et al, 2011a, 2011bRodriguez-Arias et al, 2011). This is another point of discrepancy; some studies have measured effects after very short periods postadministration (only 2 or 3 days), while others have assessed effects weeks or even months after the last administration.…”
Section: Animal Models Of Adolescent Polydrug Consumptionmentioning
confidence: 99%